Being a man in the hoods: a look at video clips of rap and rock music groups from the south of Brazil (Revista Contexto & Educação, 2024)
In this article, we aim to investigate the representations of contemporary youthful masculinities made visible in two video clips of musical groups, shared on Facebook pages targeting rock and rap audiences of a city in the interior of Rio Grande do Sul/RS. Therefore, in the text we establish some connections with Cultural Studies in their post-structuralist aspects, as well as with Gender and Masculinity Studies. In both video clips, we identify young people who are subjectivized by their local experiences, which are marked by violence and criminality. In this way, we found representations of contesting youthful masculinities, regarding to their social realities, in addition representations of resistant youthful masculinities to the practices that delimit their ways of being and living. These musical groups stress the violent actions of the State and the criminality present in their hoods, which affect the daily life of their peers.
Keywords: Masculinities; Youths; Music; Cultural Studies